#### Answer

$(0, ((-a^2/b)+b)$

#### Work Step by Step

Based on the definition of an isosceles triangle, we know that the two lines will intersect at x=0. The slope of NQ, which is perpendicular to the bisector line, is given by -2b/2a. Thus, we know that the slope of the perpendicular bisector line is: a/b We know that a point on the line is the midpoint of N and Q. Thus, we know: $M= (\frac{0+2a}{2}, \frac{0+2b}{2}) = (a,b)$
This means that the line is: $y-b = (a/b)(x-a)$ Using the same reasoning, the slope of the other perpendicular bisector is: -a/b And symmetry tells us that the equation of the other line is: $y-b = (-a/b)(x+a)$
Here, we know that the intersection point must occur at x=0. Thus, we have the equation:
$y-b = (-a/b)(x+a)$ $y-b = (-a/b)(a)$ $y = (-a^2/b)+b$
This gives the answer:
$(0, ((-a^2/b)+b)$